Co3O4@Co Nanoparticles Embedded Porous N‐Rich Carbon Matrix for Efficient Oxygen Reduction. (2nd May 2017) - Zheng, Dezhou; Zhu, Lin; Feng, Haobin; Yu, Minghao; Lu, Xihong; Tong, Yexiang
Abstract : Oxygen reduction reaction (ORR) is an important reaction in many energy conversion systems, but it is severely restricted by its slow kinetics. Developing efficient non‐noble‐metal catalysts for ORR has attracted extended interests, but still remains a great challenge. Herein, an efficient catalysts consisting of Co3 O4 @Co nanoparticles embedded in N‐rich mesoporous carbon matrix is developed by the carbonization of Co‐containing zeolitic imidazolate framework precursor. The derived matrix exhibits outstanding catalytic activity with onset potential of 0.97 V vs. RHE, half‐wave potential of 0.88 V vs. RHE, and good catalytic durability when tested with the rotation speed of 1600 rpm. Carbinization under NH3 introduces extra elemental N, which subsequently enhances the limiting current densities. This study provides insight into the rational design of highly active ORR catalysts. Abstract : An efficient catalyst consisting of Co3 O4 @Co nanoparticles embedded in N‐rich mesoporous carbon matrix is developed by the carbonization of a Co‐containing zeolitic imidazolate framework precursor. The derived matrix exhibits outstanding catalytic activity with good catalytic durability. Moreover, carbonization under NH3 is demonstrated to introduce extra pyrrolic and quaternary N, which enhances the limiting current densities.